A systematic review of digital learning resources for adolescent writing development and pedagogical integration - Sahrir, Muhammad Sabri; Ahmad Rahiman, Wan Syakirah Wan; Abdul Halim, Rosmani; Albantani, Azkia Muharom; Haji Ahmad, Siti Sara; Yani, Achmad (WSEAS Press, 2026)
This systematic literature review synthesizes empirical evidence from 43 peer-reviewed studies (2020–2025) on digital learning resources (DLRs) for developing writing skills among secondary school students. Guided by PRISMA 2020 guidelines, the review addresses three research questions concerning the types of DLRs employed, their reported impacts on writing outcomes, and the pedagogical and contextual factors influencing their implementation. Findings reveal a diversification of tools, including automated writing evaluation (AWE) systems, collaborative platforms (e.g., Google Docs), AI prompt engineering, gamified applications, and communication tools like Zoom, increasingly aligned with specific writing genres and processes. DLRs consistently enhance higher-order writing skills (e.g., argumentation, creativity, organization) and affective dimensions (e.g., self-efficacy, reduced anxiety), yet show limited impact on grammatical accuracy and cohesion. Critically, effectiveness is mediated by intentional pedagogical integration, such as metacognitive flipped classrooms, goal-setting, and visualization-enhanced collaboration, and constrained by teacher preparedness, classroom management challenges, and institutional resistance to advanced analytics. The review identifies a a Pedagogy-Over-Platform (POP) framework divided in writing development and underscores that technology’s value lies not in novelty but in thoughtful, context-responsive design, Implications for educators, researchers, and policymakers emphasize the need for balanced skill instruction, sustained professional development, and equitable access to ensure DLRs fulfill their potential as inclusive and educationally meaningful resources